Cord blood screening for Α-thalassemia and hemoglobin variants by isoelectric focusing in northern Thai neonates: Correlation with genotypes and hematologic parameters - Charoenkwan P. (2014)
We describe the screening of newborns for thalassemia and Hb variants by using isoelectric focusing (IEF) in a population from northern Thailand where hemoglobinopathies are highly prevalent. The report focuses on findings of Α-thalassemia, Hb E, and other hemoglobin variants, and their correlation with genotypes and hematologic parameters. Two-hundred and seven out of 566 newborns (36.6%) had thalassemia genes or Hb variants. Seventeen different genotypes were found. Nine cases (1.6%) of Hb H disease (five deletional Hb H diseases, two Hb H/Constant Spring diseases, one deletional Hb H disease/Hb E, carrier and one Hb H/Constant Spring disease/Hb E carrier) and one Hb E-Β-thalassemia were identified. IEF could clearly distinguish Hb H diseases and carriers of two Α-globin gene defects from normal individuals according to the presence of Hb Bart's and its percentage. For carriers of a single Α-globin gene defect, Hb Bart's was either absent or present in a small amount and was therefore not reliable for screening. The presence of an additional band at the Hb A2 position in the newborns signified an Hb E carrier. One case of an absent Hb A and a presence of Hb E was identified as Hb E-Β-thalassemia. Two Hb Q-Thailand carriers were seen with two additional Hb fractions, presumably combinations of Γ-globin and Β-globin with the Α-globin variant. Newborns with Hb H disease had lower Hb, MCV, and MCH levels than normal. MCV and MCH were also useful for differentiation of carriers of two Α-globin gene defects, but not for carriers of Hb E or single Α-globin gene defect. IEF was a reliable method for neonatal cord blood screening for Α-thalassemia and Hb variants. © 2010 Elsevier Inc.